Microencapsulation of Lactobacillus acidophilus NCIMB 701748 in matrices containing soluble fibre by spray drying: technological characterization, storage stability and survival after in vitro digestion - Yonekura, Lina; Sun, Han; Soukoulis, Christos; Fisk, Ian D. (Elsevier, 2014)
We evaluated sodium alginate, chitosan and hydroxypropyl methylcellulose (HPMC) as co-encapsulants for spray dried Lactobacillus acidophilus NCIMB 701748 by assessing their impact on cell viability and physicochemical properties of the dried powders, viability over 35 days of storage at 25 °C and survival after simulated digestion. Fibres were added to a control carrier medium containing whey protein concentrate, d-glucose and maltodextrin. Sodium alginate and HPMC did not affect cell viability but chitosan reduced viable counts in spray dried powders, as compared to the control. Although chitosan caused large losses of viability during spray-drying, these losses were counteracted by the excellent storage stability compared to control, sodium alginate and HPMC, and the overall effect became positive after the 35-day storage. Chitosan also improved survival rates in simulated GI conditions, however no single fibre could improve L. acidophilus NCIMB 701748 viability in all steps from production through storage and digestion.